Optimization of Solar and Wind Hybrid Energy System with IoT Integration for Remote Areas in Indonesia - Tahir, Usman; Darmawan, Erwan; Robbani, Farisan (Journal of Renewable Engineering, 2025)
Limited access to electricity in remote areas of Indonesia reflects complex structural issues, including geographic constraints, policy inequalities, and the low effectiveness of centralized approaches. Thousands of villages in the 3T (Disadvantaged, Frontier, and Outermost) regions still do not enjoy reliable electricity, hampering socio-economic development and reinforcing the cycle of poverty. Although Indonesia has great potential for renewable energy—such as solar and wind—its use is still minimal due to infrastructure constraints, investment, and non-contextual development approaches. In this context, a hybrid solar-wind energy system integrated with Internet of Things (IoT) technology offers an efficient and sustainable decentralized solution. IoT enables real-time monitoring, predictive maintenance, and data-driven energy management, which are critical in remote areas with limited technicians and physical access. This study uses a qualitative approach through a literature review to examine the challenges, potential, and policy relevance in developing IoT-based renewable energy systems. The results of the analysis show that transforming energy systems in marginalized areas requires not only technological innovation, but also a paradigm shift towards inclusive energy justice. Therefore, strengthening local capacity and integrating context-based policies are key to realizing a fair, reliable and sustainable energy system in Indonesia.